2005
DOI: 10.1111/j.0737-6782.2005.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Interorganizational Collaboration and Innovation: Toward a Portfolio Approach*

Abstract: In the literature on innovation, interorganizational collaboration has been advanced as beneficial for the innovative performance of firms. At the same time, large‐scale empirical evidence for such a relationship is scarce. This article examines whether evidence can be found for the idea that interorganizational collaboration supports the effectiveness of innovation strategies. This article empirically addresses this research question by analyzing data on Belgian manufacturing firms (n=221) collected in the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
865
3
30

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,003 publications
(926 citation statements)
references
References 68 publications
28
865
3
30
Order By: Relevance
“…Ryan, Mottiar, and Quinn (2012) add that entrepreneurial behaviour strongly influences tourism development by stimulating others to follow innovative behaviour. Findings from general management (Faems, van Looy, & Debackere, 2005) confirm that increased inter-organisational collaboration improves the degree of innovation of single organisations. Therefore, it can be concluded that destination management organisations are important actors to stimulate entrepreneurial behaviour of rural tourism family firms by initialising cooperation in product/service development.…”
Section: Resultsmentioning
confidence: 75%
“…Ryan, Mottiar, and Quinn (2012) add that entrepreneurial behaviour strongly influences tourism development by stimulating others to follow innovative behaviour. Findings from general management (Faems, van Looy, & Debackere, 2005) confirm that increased inter-organisational collaboration improves the degree of innovation of single organisations. Therefore, it can be concluded that destination management organisations are important actors to stimulate entrepreneurial behaviour of rural tourism family firms by initialising cooperation in product/service development.…”
Section: Resultsmentioning
confidence: 75%
“…Faems, Van Looy and Debackere, 2005;Nieto and Santamaria, 2007;Porter and Ketels, 2003). Overall, a consensus has been developed that suggests that the exclusion of participation in such networks becomes a limiting factor for enhancing a firm's knowledge base (Shaw, 1998).…”
Section: Inter-firm Networkingmentioning
confidence: 99%
“…This construct is closely related to the paradigm of open innovation (Chesbrough 2006) as Ba paradigm that assumes that firms can and should use external ideas as well as internal ideas, and internal and external paths to market, as they look to advance their technology^(p. 1). Such collectivistic firm cultures as well as cooperative approaches toward external partners can contribute considerably to a successful exploitation of opportunities to sustain competition (Eddleston et al 2008;Hollen et al 2013;Faems et al 2005).…”
Section: Hypotheses Developmentmentioning
confidence: 99%